Validation of electrochemiluminescence assays for highly sensitive and reproducible quantification of α-synuclein in cerebrospinal fluid. (April 2017) - Kruse, Niels; El-Agnaf, Omar M; Mollenhauer, Brit
Aim: α-Synuclein (aSyn), a putative cerebrospinal fluid biomarker, may support the diagnosis of neurodegenerative diseases. Previous studies led to conflicting results due to different preanalytical and analytical procedures. Standardized assays are required to allow for comparison of results from different laboratories.Materials & methods: We performed a side-by-side validation of a commercially available (MSD, MD, USA) and a 'homebrew' assay for quantification of aSyn according to published guidelines.Results: The data showed high sensitivity and reproducibility for both assays. Preanalytical and analytical parameters did not affect the outcome of measurements.Conclusion: We conclude that both assays are very close in performance and suitable for research application of cerebrospinal fluid aSyn.